CORAK TEOLOGIS-FILOSOFIS DALAM PENAFSIRAN ALQUR’AN - Ridhoul Wahidi Amaruddin (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2014)
This paper examines one mode of interpretation of the theologicalphilosophical style. Where the position of the interpreter in the theological-philosophical or later serve as the subject and the Qoran it self serve as the object of discussion, so that a trend/loaded with interests. The style of the theological-philosophical focus to discuss the themes of the theological-philosophical than forward messages that brought fundamental Qur’an.